Human Palaeoecological Interactions and Owl Roosting at Tron Bon Lei, Alor Island, Eastern Indonesia. (3rd July 2018) - Hawkins, Stuart; Samper Carro, Sofia C.; Louys, Julien; Aplin, Ken; O'Connor, Sue; Mahirta,
ABSTRACT: We report on tetrapod (Reptilia, Amphibia, Mammalia, Aves) vertebrates recovered during excavations at Tron Bon Lei rockshelter on the south coast of Alor Island, eastern Indonesia. These include both archaeological specimens recovered from a 1 m² test pit dating from ∼21 kya cal BP to the late Holocene, and a modern eastern barn owl deposit recovered nearby. To discern between the depositional processes that accumulated the small numbers of micro- and macrovertebrate remains from the archaeological deposits, the taphonomic signature of the natural assemblage was quantified and compared to the archaeological record. The taphonomic data indicates that the tetrapod archaeofaunal remains are a combination of barn owl predation of microfauna and human predation of larger fauna. This approach provides new information on human-tetrapod interactions on Alor in Wallacea during the late Quaternary, including an apparent increase in cave site use and hunting intensity during the Pleistocene-Holocene transition, sea turtle butchery and probable transport, and extinctions of previously unknown giant to large rat species.